Grundlagen der Organischen Chemie - Buddrus, Joachim; Buddrus, Joachim; Schmidt, Bernd (De Gruyter Studium, 2015)
The 5th edition of this successful textbook has been revised both in terms of content and its teaching approach. With comprehensive but simple explanations, the work provides an optimal introduction to organic chemistry. Each chapter contains numerous practice exercises and solutions, making it an excellent work for students new to the field.